Spanish Flu in Shiraz from 1918 to 1920 - Golshani, Seyyed Alireza; Golshani, Seyed Amir Hossein (Medicina Historica, 2023)
The Spanish flu outbreak is one of the historical catastrophes in Fars province, especially Shiraz, southern Iran that infected almost the entire population. The epidemic began on 29 October 1918 and continued until 1920 in several waves. Within three years, the population of Shiraz decreased from 50,000 to around 20,000-25,000. The disease killed half of the city population and caused severe damages to its demographic context and economic development. A rather unpleasant remnant of the epidemic is Javan Abad Cemetery in Shiraz. This study aimed to explore the importance of local medical history in Shiraz, the effect of the flu outbreak, World War I, and presence of the British that led to a human-made famine and malnutrition, and the role played by this colonial government in amplifying the Flu outbreak and city decimation. The study also aimed to discuss the type of the disease and treatment used by the British forces.